Knowledge, Attitude and Practice among Nurses Regarding Prevention of Central Line Associated Bloodstream Infection in Tertiary Care Hospital of Peshawar: Prevention of Central Line Associated Bloodstream Infections - Khan, Mudassir; Ahmad, Imran Waheed; Waheed, Mehwish; Tahir, Haseena; Hurain, Khush; Monica, . (Pakistan Journal of Health Sciences, 2024)
Healthcare Associated Infections (HAIs), particularly Central Line-Associated Bloodstream Infections (CLABSIs), remain a significant global public health concern. CLABSIs, associated with catheter use, pose critical challenges in critical care and cancer treatment settings, necessitating evidence-based measures for prevention. Objective: To assess the knowledge, attitude and practice of nurses regarding prevention of central line associated bloodstream infection in tertiary care hospital of Peshawar. Methods: This conducted study possessed a cross sectional study design with a random sample of 173 nurses who were presently working or had worked in ICUs of the hospital. Data were collected through a self-administered questionnaire. Data analysis was performed on SPSS version 22.0. Results: 45% of nurses demonstrated good knowledge with mean score of 12.35 and standard deviation of ± 1.45, positive attitudes were observed in 74% with mean score of 33.7 and standard deviation of ±2.1 and good practices in 80% of participants with mean score of 40.5 and standard deviation of 1.45 observe. Conclusions: This study clearly indicated that majority of the nurses (54.9%) have poor knowledge regarding CLABSI. Despite of the poor knowledge level most nurses (74%) followed standard practice. Interestingly, greater number of nurses (85%) were found to have positive attitude towards CLABSI.